2016
DOI: 10.1039/c6ra06895b
|View full text |Cite
|
Sign up to set email alerts
|

CO2 chemisorption in Li2CuO2 microstructurally modified by ball milling: study performed with different physicochemical CO2 capture conditions

Abstract: Lithium cuprate (Li 2 CuO 2 ) was obtained by a solid state reaction and a subsequent ball milling process; then, the samples were characterized structurally and microstructurally. Additionally, both the Li 2 CuO 2 ball milled and the solid state samples, for comparison purposes, were tested in the CO 2 chemisorption process at moderate and low temperatures under different reaction conditions: (i) at moderate CO 2 pressure and (ii) in the presence of water vapor. In both cases, the textural and microstructural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 38 publications
(119 reference statements)
0
13
0
Order By: Relevance
“…In the absence of oxygen supply from the air flow, oxygen atoms have to be released from the structure of lithium tungsten oxide, and this anionic crystalline diffusion could limit the carbonation process. 23 Our dynamic CO 2 sorption results indicate that Li 6 WO 6 with NW morphology has significant potential for CO 2 sorption at a range of high temperatures. The BET measurements indicate a surface area of 8.1 m 2 /g for NW powder.…”
Section: Nano Lettersmentioning
confidence: 70%
See 1 more Smart Citation
“…In the absence of oxygen supply from the air flow, oxygen atoms have to be released from the structure of lithium tungsten oxide, and this anionic crystalline diffusion could limit the carbonation process. 23 Our dynamic CO 2 sorption results indicate that Li 6 WO 6 with NW morphology has significant potential for CO 2 sorption at a range of high temperatures. The BET measurements indicate a surface area of 8.1 m 2 /g for NW powder.…”
Section: Nano Lettersmentioning
confidence: 70%
“…In line with previous reports, for the case of lithium tungstate, the oxygen from air seems to assist the carbonation process on adsorbents. In the absence of oxygen supply from the air flow, oxygen atoms have to be released from the structure of lithium tungsten oxide, and this anionic crystalline diffusion could limit the carbonation process . Our dynamic CO 2 sorption results indicate that Li 6 WO 6 with NW morphology has significant potential for CO 2 sorption at a range of high temperatures.…”
mentioning
confidence: 92%
“…In the process of CCS, CO 2 is captured from flue gas and stored for utilization and sequestration instead of being released to the environment directly. Recent studies have found that various lithium-based materials, such as LiFeO 2 [6], Li 2 CuO 2 [7], Li 2 ZrO 3 [7,8,9], Li 8 SiO 6 [10,11], and Li 4 SiO 4 [9], are capable of effective CO 2 capture. Among these materials, Li 4 SiO 4 , with a variety of applications [12,13], has better application potential, owing to its higher CO 2 sorption capacity, cyclic stability than LiFeO 2 , Li 2 CuO 2 , and Li 8 SiO 6 , and lower cost than that of Li 2 ZrO 3 [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this line, recently it has been shown that different CO 2 sorbents [19] , i.e., Na 2 ZrO 3 can be used as bifunctional materials, acting first as a CO 2 captor and then as a catalytic material for methane reforming reaction, presenting a clearly advantages over the procedure proposed by Gorin and Retallik. Other CO 2 material captors, namely alkali (Li, Na and K) [20][21][22][23][24][25] and alkalineearth (Be, Mg and Ca) [26][27][28][29] metal-based ceramics have shown high ability for CO 2 capture. Therefore, all these ceramics may be promissory carbonated materials for hydrogen production through dry methane reforming.…”
Section: Introductionmentioning
confidence: 99%